Exploring the causes of divorce among applicants and experts in the field of divorce in the city of Rasht: emphasizing the commission of crimes arising from marital maladjustment - Hojjat Falah Khajakini; Atefeh Larkjouri; Amir Reza Mahmoudi; Vahid Zarei Sharif (مجله علوم روانشناختی, 2024)
Background: Divorce is a social issue that has witnessed an upward trend in recent years, exerting negative effects on families, children, and society. One significant factor contributing to divorce is marital misconduct, which may lead to the commission of crimes related to domestic violence, assault, infidelity, and even homicide. Despite numerous studies on the causes and consequences of divorce in Iran, there is a lack of sufficient research on the role of marital misconduct in divorce occurrences. Aims: This study aims to investigate the causes of divorce reported by divorce applicants and domain experts in Rasht City, with a specific emphasis on the commission of crimes resulting from marital misconduct. Additionally, the study seeks to propose legal and psychological solutions to reduce the phenomenon of divorce. Methods: The present research adopts a descriptive-correlational approach with an applied nature. The target population includes all divorce applicants in Rasht City, from whom 200 individuals (100 men and 100 women) were randomly selected for examination of the reasons behind divorce based on their self-narratives. Moreover, domain experts in divorce, including family court judges, divorce notaries, and social workers (42 individuals in total), were included. Data were collected using a researcher-designed questionnaire through fieldwork, and the analysis involved Pearson correlation, stepwise regression, and Spearman tests in the SPSS26 software. Results: Regression analysis results indicate that the most influential factor in divorce rates is related to sexual and ethical crimes, especially illicit relationships in virtual spaces (p < 0.05). Conclusion: The findings of this study suggest that marital misconduct can lead to unlawful and criminal behaviors, impacting divorce rates. Therefore, it is recommended to focus on increasing awareness and communication skills among couples, strengthening emotional relationships, encouraging joint decision-making, supporting at-risk families, and providing suitable counseling and psychological therapy services to prevent and reduce divorce in society.